LINKING PERFORMANCE WITH SUSTAINABILITY IN PUBLIC UNIVERSITIES. THEORETICAL FRAMEWORK AND BIBLIOMETRIC ANALYSIS - ORZA (VRAJA), Mona Alexandra; NISTOR, Cristina Silvia (Studia Universitatis Babeș-Bolyai Negotia, 2025)
Linking university performance to sustainability is possible through the university’s third mission: environmental responsibility. To better understand the concepts, practices and challenges of sustainability, the role of literature is crucial; therefore, this paper reviews the existing literature on academic performance and sustainability using a bibliometric analysis for articles published in the Web of Science database between 2009 and 2023. This research intends to contribute to recent stream of research on sustainability implementation by identifying the relationship between performance and sustainability in university missions. To date, there have been only a few bibliometric analyses the relationship between performance and sustainability in the public higher education sector. However, no one has discussed the perspective of the link between performance and sustainability through the university mission, and this research intends to fill this gap. The results show that in the last three years, the interest in performance and sustainability has led to an increase of up to 66% in articles on sustainability and performance in the public university system. Spain appears to be the main contributor to the research articles related to the area of interest. Research in the public university system on concepts related to sustainability and performance is still at an early stage, yet has seen considerable progress over the past few years. JEL classification: A11; O20; Q01. Article History: Received: 21 March 2025; Reviewed: 28 April 2025; Accepted: 30 May 2025; Available online: 27 June 2025.